Estimation of Some Properties of PMMA Matrix Reinforced with Yttrium Oxide and Glass Fiber for Dental Applications (THE IRAQI JOURNAL FOR MECHANICAL AND MATERIALS ENGINEERING, 2024)
The aim of this study is to modify the performance of PMMA which is suitable for denture application. It is desirable for Polymethyl methacrylate (PMMA) to have high mechanical properties for dental applications like denture. The reinforced of PMMA with 1 wt.% glass fiber and different weight percentage of Y2O3 were estimated. Increase the mechanical and physical properties were found with increased the weight percentage of Y2O3. The maximum impact strength was obtained by using 6% Y2O3 with 1 wt.% glass fibers. The physical properties, which are included density and water absorption increased with increased the weight percentage of Y2O3 in PMMA. Furthermore, the improvement in impact strength was obtained at 6% Y2O3 was 45.48%. Finally, the SEM results show the homogenous distribution of Y2O3 in PMMA.